2020
DOI: 10.1371/journal.pone.0243738
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of extracellular vesicles onto the tube walls during storage in solution

Abstract: Short term storage of extracellular vesicle (EV) solutions at +4°C is a common practice, but the stability of EVs during this procedure has not been fully understood yet. Using nanoparticle tracking analysis, we have shown that EVs isolated from the conditioned medium of HT-29 cells exhibit a pronounced concentration decrease when stored in PBS in ordinary polypropylene tubes within the range of (0.5–2.1) × 1010 particles/ml. EV losses reach 51±3% for 0.5 ml of EVs in Eppendorf 2 ml tube at 48 hours of storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…Configuration included 405-nm, 65-mW laser unit with passive temperature readout and high sensitivity camera of EMCCD type. All measurements were performed according to ASTM E2834 ( ASTM, 2018 ), using previously reported camera- and video-processing setups, optimized for EVs ( Livshits et al, 2015 ; Silachev et al, 2019 ; Evtushenko et al, 2020 ). Briefly, samples were diluted by particle-free PBS down to the optimal concentration around 1.5 × 10 8 particles/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Configuration included 405-nm, 65-mW laser unit with passive temperature readout and high sensitivity camera of EMCCD type. All measurements were performed according to ASTM E2834 ( ASTM, 2018 ), using previously reported camera- and video-processing setups, optimized for EVs ( Livshits et al, 2015 ; Silachev et al, 2019 ; Evtushenko et al, 2020 ). Briefly, samples were diluted by particle-free PBS down to the optimal concentration around 1.5 × 10 8 particles/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers warned that isolated EVs could be adsorb onto tube walls, which would decrease EV concentration. Using Eppendorf Protein LoBind tubes or adding bovine serum albumin or Tween-20 to block the wall can decrease the loss [ 104 , 105 ]. Hermida-Nogueira et al (2020) found that seven days following a pathogen reduction technology (PRT) + Mirasol ® (vitamin B2 with ultraviolet B light), 151 proteins, including EV markers and regulatory proteins released by platelets, were upregulated compared to their levels after two days of storage [ 106 ].…”
Section: Biofluids and Extracellular Vesicles Characterization Under ...mentioning
confidence: 99%
“…These are more likely to occur for purified vesicles. [50][51][52] However, there is not a consensus on a method to suppress nonspecific adsorption of EVs. Here, we consider a blocking treatment with excess protein or hydrophilic polymers as a practical solution to prevent nonspecific binding in various bioanalytical methods.…”
Section: Suppression Of Nonspecific Ev Adoption To Spm By a Blocking ...mentioning
confidence: 99%